RAB27A‐dependent release of exosomes by liver cancer stem cells induces Nanog expression in their differentiated progenies and confers regorafenib resistance. Issue 12 (9th August 2021) - Huang, Hongxia; Hou, Jue; Liu, Kewei; Liu, Qin; Shen, Liting; Liu, Biying; Lu, Qian; Zhang, Ni; Che, Linrong; Li, Jinyang; Jiang, Shan; Wang, Bin; et al.
Abstract: Background and Aim: Regorafenib is a potent multikinase inhibitor for the second‐line targeted therapy against hepatocellular carcinoma (HCC); however, drug resistance is emerging in clinical settings. Although cancer stem cells (CSCs) are considered as key determinate of drug sensitivity, it remains unclear how CSCs may communicate with the differentiated counterparts (non‐CSC) to dictate therapeutic efficacy. Therefore, we sought to investigate the regorafenib resistance mechanism of CSCs in HCC. Methods: We used sphere formation and soft agar colony formation assays to evaluate the stemness capacity of cancer cells. Cell viability assay was performed to detect the sensitivity of cancer cells to regorafenib. Real‐time quantitative polymerase chain reaction and western blot were used to analyze gene expression. Mouse xenograft tumor model was performed to assess Regorafenib sensitivity in vivo . Results: Exosomes are highly enriched in CSC supernatant compared with that of non‐CSC, and RAB27A mediates exosome secretion from CSCs to maintain stem‐like phenotype and regorafenib insensitivity. Moreover, exosomes released by CSCs upregulate the expression of Nanog in non‐CSC, while depleting Nanog sensitizes non‐CSC to regorafenib in the presence of CSC exosomes. Consistently, analysis of TCGA datasets reveals that RAB27A expression tightly correlates with Nanog in HCC tissues. More importantly, depletion of RAB27A downregulates Nanog expression and sensitizes cancer cells to regorafenib in nude mice. Conclusions: Our findings suggest that CSCs release exosomes in a RAB27A‐dependent manner to induce Nanog expression and regorafenib resistance in differentiated cells, targeting this exosome signaling between distinct cellular subsets may be a potential therapeutic strategy for HCC patients.